2020
DOI: 10.3389/fpsyt.2019.00991
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Treatment Outcome in Anorexia Nervosa: A Scoping Review of the Literature

Abstract: Alexithymia is of great interest as an outcome predictor of recovery from anorexia nervosa, since it may interfere with both treatment compliance and patients' ability to benefit from the adopted interventions. For this reason, in the last years new treatment approaches targeting emotion identification, expression, and regulation have been applied and tested. Using the PRISMA methodology, we performed a scoping review of the literature about treatment outcome in anorexia nervosa, in terms of changes in alexith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…Notably, reliable change analyses indicated that only 25% of the sample reported reliable decreases in symptoms from intake to discharge. Altogether, these results are generally consistent with the conclusions from a recent review on alexithymia within treatment for anorexia nervosa (Gramaglia et al., 2020) and other forms of psychopathology (Cameron et al., 2014), which suggest small changes in alexithymia over the course of treatment. Our findings represent the first investigation of changes in alexithymia in a DBT‐informed EDs programme, although it is important to note that we cannot attribute changes in alexithymia to DBT, given that this was a naturalistic study without a control group and our findings may be accounted for by regression to the mean.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, reliable change analyses indicated that only 25% of the sample reported reliable decreases in symptoms from intake to discharge. Altogether, these results are generally consistent with the conclusions from a recent review on alexithymia within treatment for anorexia nervosa (Gramaglia et al., 2020) and other forms of psychopathology (Cameron et al., 2014), which suggest small changes in alexithymia over the course of treatment. Our findings represent the first investigation of changes in alexithymia in a DBT‐informed EDs programme, although it is important to note that we cannot attribute changes in alexithymia to DBT, given that this was a naturalistic study without a control group and our findings may be accounted for by regression to the mean.…”
Section: Discussionsupporting
confidence: 90%
“…Within EDs, research on alexithymia within the context of treatment is limited (Gramaglia et al., 2020). A recent review of a small body of existing work (i.e., n = 11 studies) suggests that alexithymia may relate to worse outcomes at discharge (Vrieze, 2018) and follow‐up (Speranza et al., 2007), but is somewhat amenable to intervention (Becker‐Stoll & Gerlinghoff, 2004; Gramaglia et al., 2020; Tchanturia et al., 2015). A recent paper from our group suggested that alexithymia had a unique impact on emotion dysregulation over time in individuals with anorexia nervosa (Brown, Avery, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, alexithymic characteristics were found in various clinical conditions characterized by a disordered affect regulation ( 5 ), such as depression ( 16 ), self-harm and suicidality ( 17 19 ), schizophrenia ( 20 ), eating disorders ( 21 , 22 ), substance use disorder ( 23 ) and autism spectrum disorder ( 24 , 25 ). Hence, alexithymia started to be considered a non-specific vulnerability factor involved in the development of physical and mental disorders as well as a specifier associated with adverse outcomes when treating such conditions [see e.g., ( 26 , 27 )]. Concurrently, alexithymia was associated with several medical conditions such as diabetes, cancer or chronic illnesses ( 28 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study aims to evaluate whether general and specific psychopathology is worsened by the presence of alexithymia, as the current literature suggests (Gramaglia et al, 2020), and to determine if a multidisciplinary inpatient treatment for EDs can reduce alexithymia and dissociation. Finally, we aim to point out possible relationships among specific and general psychopathological target variables.…”
mentioning
confidence: 99%